Extraskeletal Myxoid Chondrosarcoma with Small Bowel Metastasis Causing Bowel Obstruction - Ernesto Bustinza-Linares; Francisco Socola; Vinicius Ernani; Shelly A. Miller; Jonathan C. Trent (Case Reports in Oncological Medicine)
A 28-year-old female with history of chest wall extraskeletal myxoid chondrosarcoma (EMC) presented to the emergency department complaining of two weeks of lightheadedness and fatigue. Laboratories showed hemoglobin of 7.6 g/dL and a positive hemoccult test. Upper and lower endoscopies were unremarkable, and the patient was discharged after blood transfusion. The next day she returned to the ED with left-sided weakness and perioral numbness. Brain CT scan revealed a 6 cm right frontal mass with midline shift and edema that required urgent craniotomy with resection of a hemorrhagic tumor. The patient continued dropping her hemoglobin, and CT scans showed a rounded 3 cm small bowel mass in the mid ileum. Repeat upper endoscopy revealed a 2 × 2 cm ulcerated mass in the fourth portion of the duodenum. The patient was taken to the operating room and was found to have two lesions; one in the distal duodenum and a second one in the mid ileum causing small bowel intussusception. Pathology was consistent with metastatic EMC grade 2/3, involving the bowel and mesenteric fat. Extraskeletal myxoid chondrosarcoma (EMC) is a rare soft-tissue sarcoma with unique features that distinguishes, it from other sarcomas. It has been often described as a low-grade sarcoma although there are certain characteristics like high mitotic activity and the presence of focal regions of Ki67 staining above 25% that correlate with aggressive behavior of the tumor. This is the first case of EMC metastatic to the small bowel to be reported to the medical community.